Self-reportance of temporomandibular disorders in adult patients attending general dental practice in Sweden from 2011 to 2013. (3rd October 2018) - Adèrn, Bengt; Minston, Ava; Nohlert, Eva; Tegelberg, Åke
Abstract: Objectives: The study aim was to evaluate the prevalence of self-reported temporomandibular disorders (TMD) and acceptance or nonacceptance of such disorders in adult patients attending all public dental health services in the County of Sörmland, Sweden, during a 3-year period, 2011–2013. Methods: Two questions were asked about TMD and the voluntary mouth-opening capacity was measured. The results were registered in a score 0–3. The registration was completed with a question about each patient's acceptance or nonacceptance of their condition. Results: More than 73, 000 registrations of the TMD condition were performed in general dental clinics from 2011 to 2013. The mean prevalence of a TMD score of 1–3 was 5% and was consistent over these years. Seventy percent of these patients were women. The peak prevalence of TMD was registered in patients aged 30–45 years (38%), and the frequency declined in older age groups. Reduced voluntary mouth-opening capacity (≤35 mm) was found in less than 2% of the participants. About one-fifth of the patients with a TMD-score of 1–3 did not accept their condition and wanted professional care. The frequency of nonacceptance of the condition increased with the severity of symptom score: 15%, 27%, and 49% for scores 1, 2, and 3, respectively. Conclusions: This study shows that the prevalence of self-reported TMD in adult patients was consistent from 2011 to 2013 and should be considered as a public health issue in Sweden. Patients with more severe TMD pain symptoms wanted care more frequent. The annual clinical calibrations should be continued to achieve an acceptable level of registration.